2021
DOI: 10.3390/ijms22094705
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying TDP-43 Pathology in Cellular and Animal Models of ALS and FTLD

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are neurodegenerative disorders that exist on a disease spectrum due to pathological, clinical and genetic overlap. In up to 97% of ALS cases and ~50% of FTLD cases, the primary pathological protein observed in affected tissues is TDP-43, which is hyperphosphorylated, ubiquitinated and cleaved. The TDP-43 is observed in aggregates that are abnormally located in the cytoplasm. The pathogenicity of TDP-43 cytoplasmic aggregates may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 216 publications
(415 reference statements)
0
38
0
1
Order By: Relevance
“…A survey of 56 RBPs in the immortalized Schneider 2 (S2) cell culture line derived from late-stage Drosophila embryos found that individual RBPs can regulate from tens to hundreds of splice events [24], while studies in vertebrates suggest that CELF (CUG-BP and Etr-3-like factor), RBFOX (RNA binding Fox-1 homolog) and MBNL (muscleblind-like) family proteins may regulate hundreds to thousands of events in muscle [25,26]. TDP-43 (TAR DNA-binding protein 43), which is associated with neurodegenerative disorders, inclusion body myositis and rimmed vacuole myopathies, regulates alternative splicing as well as mRNA trafficking and translation and mRNP granule formation [27,28]. CELF and MBNL proteins, which have well-characterized roles during muscle development, regulate mRNA stability, translation and localization in addition to alternative splicing [26,29,30].…”
Section: Regulation Of Rbps Modulates Rna Processing In Musclementioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 56 RBPs in the immortalized Schneider 2 (S2) cell culture line derived from late-stage Drosophila embryos found that individual RBPs can regulate from tens to hundreds of splice events [24], while studies in vertebrates suggest that CELF (CUG-BP and Etr-3-like factor), RBFOX (RNA binding Fox-1 homolog) and MBNL (muscleblind-like) family proteins may regulate hundreds to thousands of events in muscle [25,26]. TDP-43 (TAR DNA-binding protein 43), which is associated with neurodegenerative disorders, inclusion body myositis and rimmed vacuole myopathies, regulates alternative splicing as well as mRNA trafficking and translation and mRNP granule formation [27,28]. CELF and MBNL proteins, which have well-characterized roles during muscle development, regulate mRNA stability, translation and localization in addition to alternative splicing [26,29,30].…”
Section: Regulation Of Rbps Modulates Rna Processing In Musclementioning
confidence: 99%
“…Despite the hundreds of proteins identified to bind RNA or contain canonical RNAbinding domains [20,35,36], our understanding of RNA regulatory dynamics is still vastly incomplete as relatively few RBPs have been studied extensively in muscle. Most wellstudied RBPs in muscle are associated with or causal for muscle diseases, notably CELF1 and MBNL1 (myotonic dystrophy) [37], SMN (spinal muscular atrophy) [38], TDP-43 [28], and Rbm20 and Rbm24 (dilated cardiomyopathy) [39]. We recently found that only 82 RBPs have been studied in muscle in any model organism, which is far less than the hundreds of annotated RBPs expressed in transcriptomic data from muscle [11].…”
Section: Drosophila As a Model To Identify And Study Muscle-specific Rbp Functionmentioning
confidence: 99%
“…The phosphorylation of peptides associated with ND proteinopathies is a key process for their toxic aggregation, accumulation, and further cognitive deficits [93,[316][317][318], which has been addressed by various studies. A metallic nanosystem of AuNPs reduces Tau phosphorylation and improves mitochondrial antioxidant balance and ETC complex activity along with the recovery of cognitive impairment in a rat AD model induced by intracerebral administration of okadaic acid [288].…”
Section: Interfering With Protein Aggregationmentioning
confidence: 99%
“…A survey of 56 RBPs in Drosophila S2 cells found that individual RBPs can regulate from tens to hundreds of splice events [24], while studies in vertebrates suggest that CELF, RBFOX and MBNL may regulate hundreds to thousands of events in muscle [25,26]. TDP-43, which is associated with neurodegenerative disorders as well as inclusion body myositis and rimmed vacuole myopathies, regulates not only alternative splicing but also mRNA trafficking and translation and mRNP granule formation [27,28]. CELF and MBNL proteins regulate mRNA stability, translation and localization in addition to alternative splicing [26,29,30].…”
Section: Regulation Of Rbps Modulates Rna Processing In Musclementioning
confidence: 99%
“…Despite the hundreds of proteins identified to bind RNA or contain canonical RNAbinding domains [20,35,36], our understanding of RNA regulatory dynamics is still vastly incomplete as relatively few RBPs have been studied extensively in muscle. Most wellstudied RBPs in muscle are associated with or causal for muscle diseases, notably CELF1 and MBNL1 (myotonic dystrophy) [37], SMN (spinal muscular atrophy) [38], TDP-43 [28], and Rbm20 and Rbm24 (dilated cardiomyopathy) [39]. We recently found that only 82 RBPs have been studied in muscle in any model organism, which is far less than the hundreds of annotated RBPs expressed in transcriptomics data from muscle [11].…”
Section: Drosophila As a Model To Identify And Study Muscle-specific Rbp Functionmentioning
confidence: 99%